Endoscopic Management of Obstruction due to an Acquired Bronchial Web - Kevin L Kovitz; Mahtab B Foroozesh; Jose M Goyos; Edmundo R Rubio (Canadian Respiratory Journal)
Bronchial webs are thin, membrane-like diaphragms that may obstruct the airway. Several congenital cases have been reported. Though rare, the true incidence of these lesions is probably underestimated because many of them are unrecognized. The case of a 71-year-old woman with an acquired bronchial web causing right main stem bronchus obstruction that went unrecognized for 47 years post-trauma is reported. The lesion was successfully treated using rigid bronchoscopy with laser therapy, balloon dilation and stent placement. This is the first reported case of an acquired bronchial web formation. It is also the first reported case that was successfully treated with this technique.